Tekst piosenki jako dzieło literackie — dzieło literackie jako tekst piosenki. Zarys problematyki, przykłady realizacji - Sobczak, Paweł (Acta Universitatis Lodziensis. Folia Litteraria Polonica, 2012)
The subject of this article is the relationship between literature and the text of song. First part of article concerns the songs which texts approach to literature and begin to exist in the listeners' consciousness independently from the melody. In contemporary Polish music are this: Niech żyje bal, Autobiografia, Nie pytaj o Polskę or Wychowanie. Texts of these songs are analysed and interpreted. Second part of article tells about poems which serve as texts of songs. The author of article shows twentieth-century Polish poets, which texts be sung (Julian Tuwim, Konstanty Ildefons Gałczyński, Edward Stachura, Ewa Lipska etc.) and using with poems musicians (Czesław Niemen, Marek Grechuta, Ewa Demarczyk, Grzegorz Turnau). The author writes also about methods of adaptation of poems on need of songs.